2013
DOI: 10.1371/journal.pone.0076541
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Inhibition of Stellate Cell Activation Pathways by PPAR-γ, RAR and RXR Agonists

Abstract: Peroxisome proliferator activator receptors (PPAR) ligands such as 15-Δ12,13-prostaglandin L(2) [PJ] and all trans retinoic acid (ATRA) have been shown to inhibit the development of liver fibrosis. The role of ligands of retinoic X receptor (RXR) and its ligand, 9-cis, is less clear. The purpose of this study was to investigate the effects of combined treatment of the three ligends, PJ, ATRA and 9-cis, on key events during liver fibrosis in rat primary hepatic stellate cells (HSCs). We found that the anti-prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Among these many events, intracellular inflammasome activation is increasingly recognised as an important transducer of signals derived from inflammatory cells that is especially relevant to fatty liver disease. 20 Another emerging signalling network is the nuclear receptor family, including farnesoid-X-receptor (FXR), 21 peroxisome proliferator-activated receptors (PPAR), 22 vitamin D receptor (VDR), 23 retinoid receptors, 22 Rev-erbα 24 and liver-X-receptor (LXR). 25 Other transcriptional events contributing to stellate cell activation include Wnt/β-catenin signalling, 26 GATA4 27 and hedgehog signalling.…”
Section: Mechanisms Of Stellate Cell Activationmentioning
confidence: 99%
“…Among these many events, intracellular inflammasome activation is increasingly recognised as an important transducer of signals derived from inflammatory cells that is especially relevant to fatty liver disease. 20 Another emerging signalling network is the nuclear receptor family, including farnesoid-X-receptor (FXR), 21 peroxisome proliferator-activated receptors (PPAR), 22 vitamin D receptor (VDR), 23 retinoid receptors, 22 Rev-erbα 24 and liver-X-receptor (LXR). 25 Other transcriptional events contributing to stellate cell activation include Wnt/β-catenin signalling, 26 GATA4 27 and hedgehog signalling.…”
Section: Mechanisms Of Stellate Cell Activationmentioning
confidence: 99%
“…In HSCs, all-trans retinoic acid (ATRA) (an RAR ligand) moderately inhibits expression of procollagen I, III, IV, fibronectin, laminin, αSMA, TGFβ, and IL-6, but with no effect on cell proliferation, whereas 9-cis (RXR ligand) moderately inhibits proliferation without affecting the fibrogenic gene expression in rodents [229, 230]. These receptors, also together with PPARγ signaling, have additive inhibitory effects on HSC activation [231, 232]. RXR can form heterodimer with VDR to transmit signal from p62 in HSCs to promote fibrogenesis and inflammation, and support carcinogenesis [224].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…One study demonstrated the benefits of fibrates in patients with PSC [33]. Activation of RXR and RAR by all-trans retinoic acid (ATRA) has potent anti-fibrotic effects [34,35,36,37,38]. ATRA treatment repressed CYP7A1 promotor activity [39], which was potentiated by UDCA co-treatment [40].…”
Section: Fxr (And Other Future Therapies) In Treatment Of Cholestaticmentioning
confidence: 99%